CCR4 plays a pivotal role in Th17 cell recruitment and expansion in a mouse model of rheumatoid arthritis. (23rd August 2022) - Honzawa, Tatsuma; Matsuo, Kazuhiko; Hosokawa, Shunya; Kamimura, Mayu; Kaibori, Yuichiro; Hara, Yuta; Nagakubo, Daisuke; Oiso, Naoki; Kawada, Akira; Otsuka, Atsushi; Yoshie, Osamu; Nakayama, Takashi
Abstract: T helper 17 (Th17) cells express CC chemokine receptor 4 (CCR4) and secrete cytokines such as interleukin-17A (IL-17A) and granulocyte macrophage colony-stimulating factor (GM-CSF), while dendritic cells (DCs) produce CC chemokine ligand 22 (CCL22), a CCR4 ligand, upon stimulation with GM-CSF. Th17 cells are known to play a critical role in the pathogenesis of rheumatoid arthritis (RA). CCL22 has also been shown to be up-regulated in the synovial tissues of RA patients. Here, we investigated the role of CCR4 in collagen-induced arthritis (CIA), a mouse model of RA. DBA/1J mice efficiently developed CIA as shown by erythema, paw swelling, joint rigidity, and joint destruction. Th17 cells were increased in the arthritic joints and regional lymph nodes (LNs) of CIA mice. A fraction of Th17 cells were also shown to produce GM-CSF. On the other hand, we observed no significant increases of Th2 cells or Treg cells, the T cell subsets also known to express CCR4, in these tissues. We further observed clusters of CCR4-expressing memory Th17 cells and CCL22-producing DCs in the regional LNs of CIA mice, supporting the role of the CCR4-CCL22 axis in the expansion of Th17 cells in the regional LNs. Compound 22, a CCR4 inhibitor, ameliorated the disease severity with reduction of Th17 cells in the arthritic joints and regional LNs and Th17-DC clusters in the regional LNs. We further confirmed that CCR4-deficient mice in the C57BL/6J background were highly resistant to CIA induction compared with wild-type mice. Collectively, CCR4 contributes to the pathogenesis of CIA and may thus represent a new therapeutic target for RA. Abstract : CCR4 is crucial for the pathogenesis of arthritis Graphical Abstract: